Cartografia da cidade em suas múltiplas passagens : Várzea Grande (1970 – 1990) - Sarat, Tatiane Rosa (2010)
The protagonist of this plot is the city Várzea Grande, which experienced in its territory most of the important events that transformed the state of Mato Grosso into the giant of agribusiness worldwide. Várzea Grande for its strategic geographical location was the passage of migrants who came from all regions of Brazil, sensitized by the policies of occupation of the Amazon territory during the dictatorial period. Thus, we entered a city that was expanded in a totally disordered way. We followed the trajectories of migrants who were "out” of the ideal of the migrant / settler engendered by the dictators who, having only the workforce, blood and sweat, built the title" Industrial City "for the poor neighbor of the Capital. Seeking to supply the basic necessities of existence (housing and work), Várzea Grande became the second largest city in Mato Grosso. Highlighting the multiplicity of cultures that constituted a true “Babel” of accents, customs and cultural practices